Fulfillment of the Principle of Transparency Due to the Transfer of Receivables with Wakalah Al-Mutlaqah Without the Customer's Knowledge in Islamic Banking - Utary Maharany Barus; Tengku Keizerina Devi Azwar; Montayana Meher (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study discusses the fulfillment of the principle of transparency in the practice of transferring receivables through the wakalah al-mutlaqah contract carried out by Islamic banking without the knowledge of customers. Transparency is a fundamental principle in Islamic banking activities as a form of protection of customer rights. However, in practice, the transfer of receivables originating from financing contracts is often carried out through the granting of general power of attorney (wakalah al-mutlaqah) to a third party without notification or explicit consent from the customer as an interested party. The purpose of this study is to analyze the compliance of this practice with Islamic principles and applicable laws and regulations, and to assess the extent to which the principle of transparency is fulfilled. This study uses a normative juridical method with a statutory approach, a conceptual approach, and a case approach. The results of the study indicate that although the transfer of receivables through wakalah al-mutlaqah is permitted under Islamic jurisprudence, its implementation without notification to the customer has the potential to ignore the principle of transparency and can lead to disputes. Therefore, it is necessary to strengthen internal regulations in Islamic banking so that the receivables transfer process continues to prioritize the principles of transparency and consumer protection in the Islamic financial system in Indonesia.